Memory CD4 T cells induce selective expression of IL-27 in CD8+ DC and regulate homeostatic naïve T cell proliferation - Do, Jeong-su (2011)
Naïve T cells undergo robust proliferation in lymphopenic conditions, while they remain quiescent in steady-state conditions. However, a mechanism by which naïve T cells are kept from proliferating under steady-state conditions remains unclear. Here we report that memory CD4 T cells are able to limit naïve T cell proliferation within lymphopenic hosts by modulating stimulatory functions of DC. The inhibition was mediated by IL-27, which was primarily expressed in CD8+ DC subsets as the result of memory CD4 T cell-DC interaction. IL-27 appeared to be the major mediator of inhibition as naïve T cells deficient in IL-27R were resistant to memory CD4 T cell mediated inhibition. Finally, IL-27-mediated regulation of T cell proliferation was also observed in steady-state conditions as well as during Ag-mediated immune responses. We propose a new model for maintaining peripheral T cell homeostasis via memory CD4 T cells and CD8+ DC-derived IL-27 in vivo.